Research on the Reasonable Coal Pillar Width and Surrounding Rock Supporting Optimization of Gob-Side Entry under Inclined Seam Condition. (19th May 2021) - Jiang, Li-li; Yang, Zeng-qiang; Li, Gang-wei
Abstract : In order to study the optimal coal pillar width and surrounding rock control mechanism of gob-side entry under inclined seam condition, the 130205 return air entry adjacent to 130203 gob in Yangchangwan No. 1 well is taken as a typical engineering background. By means of engineering background analysis, theoretical analysis based on inside and outside stress field, numerical simulation by FLAC 3D software, and in situ industrial test and relevant monitoring methods, the optimal coal pillar width and surrounding rock control technology are obtained. The results show that the influence range of inside stress field is about 12.2∼12.8 m based on theoretical calculation result; under the influence of 10 m coal column, the overall deformation of the roadway is relatively small and within the reasonable range of engineering construction, so the width of the coal pillar along the return air roadway is set to 10 m which is more reasonable; the cross-section characteristics of special-shaped roadway lead to asymmetric stress distribution and fragmentation of surrounding rock, and then the asymmetric surrounding rock control technology under the coupling effect of roof prestressed anchor + high-strength single anchor cable + truss anchor cable support is proposed. The monitoring results of this support method are effective for the maintenance of gob-side entry, and the study conclusions provide new guidance for the surrounding rock control mechanism of gob-side entry under inclined seam conditions.